Antibacterial force of the luting-type of glass ionomer cement toward Lactobacillus species and Streptococcus mutans - Dwi Warna Aju Fatmawati; Ekiyantini Widyowati (Dental Journal (Majalah Kedokteran Gigi), 2007)
Rigid restoration is attached within oral cavity using adhesive cement layer. The hardening adhesive cement fills and tights the rough tooth surface with reciprocal opposing restorations. The luting type of glass ionomer cement was mostly used in the clinic for crown cementation as well as poured restoration. We can be taken a problem how strong is antibacterial effect of the luting type of glass ionomer cement to Lactobacillus species and Streptococcus Mutans. The purpose of the research was to know the antibacterial force of the luting-type of glass ionomer cement toward Lactobacillus species and Streptococcus mutans. This research was a laboratory experiment. The samples of the research were divided into two groups, treated-group (Fuji and Shofu) and controlled-group. The numbers of samples in each group consisted of 7 pieces. Taking 0,5 ml of artificial saliva in which the sample of the luting-type of glass ionomer cement (5 mm in diameter and 2 mm thick) had been immersed and storing it into Petri dish containing warm MRSA and 0,1 ml Lactobacillus sp. using poured technique. The mixture was subsequently incubated, and the colony was counted on the observation of 1st day, 7th day, and 14th day. The data were analyzed using ANOVA and LSD. The result of the research showed that the greatest mean value of the bacterial colony presented in the controlled-group and the smallest was in the group of Shofu. Statistical analysis showed a significant difference (p < 0.05). The released fluoride from glass ionomer cement occurred in the damaging phase caused by polyacrylate that released H+ ion from carboxyl group (COOH). The fluoride influenced the growth of bacteria by decelerating the activity of gycolytic enolase enzyme. The luting-type of glass ionomer cement had antibacterial force toward Streptococcus mutans and Lactobacillus sp. The luting-type of glass ionomer cement of Shofu possessed greater antibacterial force than Fuji and controlledgroup.